AN ANALYSIS OF STUDENTS’ EQUIVALENCE IN TRANSLATING ENGLISH IDIOM INTO BAHASA INDONESIA - Hanifah, Azizah Khusnul (English Education: Jurnal Tadris Bahasa Inggris, 2018)
The students of Translation English into Bahasa Indonesia Class atthe fifth semester at Raden Intan State Islamic University Lampung aresupposed to be able to use idiom. However, most of students still faceddifficulties to know the meaning of idiom and the students do not recognizeidioms within the sentences, so the students translate idioms literally.Therefore, this research was intended to analyze the student equivalence intranslating English idiom into bahasa Indonesia. This research wasconducted based on descriptive qualitative analysis. The subjects of theresearch were fifth semester at Raden Intan State Islamic UniversityLampung, while as the sample is the Translation English into BahasaIndonesia class. In collecting the data, the researcher used students result oftranslation idiom English into bahasa Indonesia. After collecting the data,researcher analyzed the students equivalence in translating English idiominto bahasa Indonesia. From the data analysis, it was found that the studentsdid not translate the sentences of the English idiom into bahasa Indonesia isthe highest frequency with the percentage is 50.76%. The second is thestudents translated with the percentage is 49.21% with details are thestudents translated by non-equivalence with the percentage is 15.89%. Then,by the equivalence with the percentage is 33.32% with details are dynamicequivalence with the percentage is 32.56%. The last with the lowestpercentage is formal equivalance with the percentage is 0.76%. From thedata showed the students had difficulities in translating English idiom intobahasa Indonesia and the students cannot maintains the meaning of theidiom, so the meaning in the source text cannot be transfered as natural aspossible in target text.Keyword: analysis, idiom, translation, descriptive qualitative, equivalance